2019
DOI: 10.4236/ijcm.2019.1011047
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Therapeutic Model of Sepsis and Purulent-Inflammatory Diseases

Abstract: In this study, the method of fluorescence spectroscopy was used to improve the diagnostics and prediction of sepsis, pyo-inflammatory diseases and postpartum endometritis. At the first stage of the study, the researcher explored the fluorescence spectra of dilutions of serum with centrifuged and non-centrifuged bacterial culture (6-day crop sugar broth with Staphylococcus aureus), distilled water, 20% albumin and sugar broth. The focus was on the influence of treatment, including infusion therapy, on the fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…During our investigation we were able to determine that a structurally altered albumin would lead to alterations in blood serum fluorescence. Due to the fact that aforementioned method allowed us to determine changes in blood serum within a timespan between 24 -48 hours prior to any clinical signs, we can confirm that it be suc-cessfully implied in sepsis diagnosis [2] [11] and monitoring.…”
Section: Literature Reviewmentioning
confidence: 68%
See 1 more Smart Citation
“…During our investigation we were able to determine that a structurally altered albumin would lead to alterations in blood serum fluorescence. Due to the fact that aforementioned method allowed us to determine changes in blood serum within a timespan between 24 -48 hours prior to any clinical signs, we can confirm that it be suc-cessfully implied in sepsis diagnosis [2] [11] and monitoring.…”
Section: Literature Reviewmentioning
confidence: 68%
“…Numerous publications were dedicated to this topic, as such they were mostly highlighting optimisation of the existing therapies involving antibiotics. However unfortunately, evaluation of the prognosis and early diagnosis of development of PPPID were severely neglected [2].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies of the fluorescence spectra of this patient showed, that bacteremia was not overcome. Although (see Figure 2, curves 3, 4 Note, that for the first time we obtained fundamental results for the fluorescence spectra of a patient with sepsis and studied the dynamics of their changes during her recovery [15] [16]. They became a reference point for our further studies of the fluorescence spectra of BS of patients with purulent-inflammatory diseases and sepsis.…”
Section: Research Resultsmentioning
confidence: 99%
“…Albumin is mainly an extracellular protein. 40% of albumin is contained in blood plasma, and 60% in the depo (40% in the skin, 20% in the muscles of the internal organs) 20 .…”
Section: Features Of Changes In Albumin Molecules In Purulent-inflammmentioning
confidence: 99%